"Saudades da festa!": Triggering sensory memories of DIY electronic music through multimodal practices. Issue 3 (September 2021) - Leaha, Mihai Andrei
DIY electronic music parties in São Paulo are deeply immersive, corporeal and sensorial. In March 2020, due to the pandemic, the parties stopped, and the scene gradually moved online manifesting itself on a new type of canvas. However, the digital manifestations of the virtual scene lost their performative and multisensorial appeal. By using multimodal elicitation methods (photos, videos, audio tracks, internet memories) this article is exploring the triggered or involuntary memory of embodied and sensorial affects that are being recalled and missed by the "clubbers." The article intends to exhibit autoethnographic memories of party participation while problematizing the way in which the memory of this missed intense experience comes from a regular attendance to electronic music gatherings and its relationship with the complex feeling of "saudade."